PERBANDINGAN LAYANAN GRATIS CHATGPT, GEMINI, DAN DEEPSEEK DALAM PENYUSUNAN PROPOSAL SKRIPSI: STUDI EKSPERIMEN PROMPT. - Sahidin; Ilhan Fauzan; Romadhon Haris Alfian; Fathan Ramadhan; Ahmad Nursodiq (Journal of Research and Publication Innovation, 2025)
This research aims to compare the free services of three AI platforms—ChatGPT, Gemini, and DeepSeek—in assisting undergraduate students in developing thesis proposals. The comparison was carried out using a unified prompt: